HUBUNGAN KOORDINASI MATA DAN KAKI TERHADAP AKURASI SMASH KEDENG DALAM PEMAINAN SEPAK TAKRAW DI SMA NEGERI 1 BENAI - Zuhrisal misrayadi; Zainur Zainur; Niputu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to determine whether there is a relation between eye and foot coordination on the accuracy of the kedeng smash, that male students who take the extracurricular football takraw at SMA Negeri 1 Benai. The sample of this study were all male students who took the football extracurricular activities at SMA Negeri 1 Benai totaling 8 people. The sampling technique was taken (total sampling) or the full sampling technique of male students who took part in the extracurricular activities at SMA Negeri 1 Benai, totaling 8 people. The results of the correlation between male students who took the takraw extracurricular activities at SMA Negeri 1 Benai where the analysis concluded that there was a relation between variable X and variable Y, it was obtained that rcount = 0.427> rtable = 0.754 so there was no relation between variable X and variable Y.Thus Ha rejected. the conclusion of the hypothesis is accepted at the level ɑ = 0.05, in other words there is no significant relation between eye and foot coordination on the accuracy of the kedeng smash on the takraw players of SMA Negeri 1 Benai. To find out the magnitude of the relationship between the two variables, namely eye and foot coordination on the accuracy of the smash, it is necessary to square the correlation coefficient value (r) multiplied by one hundred (r2x 100%), from the results of the statistical analysis carried out the value (R) = 0.961, means eye and foot coordination to the accuracy of the smash of kedeng by 18.23%.Key Words: Eye and Foot Coordination and Kedeng Smash Accuracy, Kedeng Smash Accuracy